2017
DOI: 10.1242/jeb.146498
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and embryo phenotype: is there experimental evidence for strong integration of the antioxidant system?

Abstract: Organisms have evolved complex defense systems against oxidative stress. Bird eggs contain maternally derived antioxidants that protect embryos from oxidative damage. The antioxidant system components are thought to be integrated, but few studies have analyzed the covariation between antioxidant concentrations, embryo 'oxidative status' and morphology. In addition, no study has tested the effects of experimental change in yolk antioxidant concentration on other antioxidants, on their reciprocal relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Thus, neither dietary nor IO administration of α-tocopherol affected the carotenoid concentrations of chick tissues, with no effect of α-tocopherol on the carotenoid concentrations in the RYS in the present study. Similar results were reported by Possenti et al (2017), who tested the effect of in ovo vitamin E on the distribution and use of other antioxidants and on oxidative status markers in the yolk and focal organs. They found that embryo growth was positively associated with antioxidant concentrations; however, an experimental increase in egg vitamin E level did not affect the relationships between other antioxidants or the markers of oxidative status and vitamin E concentration.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, neither dietary nor IO administration of α-tocopherol affected the carotenoid concentrations of chick tissues, with no effect of α-tocopherol on the carotenoid concentrations in the RYS in the present study. Similar results were reported by Possenti et al (2017), who tested the effect of in ovo vitamin E on the distribution and use of other antioxidants and on oxidative status markers in the yolk and focal organs. They found that embryo growth was positively associated with antioxidant concentrations; however, an experimental increase in egg vitamin E level did not affect the relationships between other antioxidants or the markers of oxidative status and vitamin E concentration.…”
Section: Discussionsupporting
confidence: 84%
“…Such early maternal effects, which may be adaptive or, conversely, reflect constraints on the ability of mothers to produce eggs of optimal composition, have therefore attracted the interest not only of animal production and physiology researchers but also of ecologists and evolutionary biologists. Importantly, egg compounds are expected to act in concert on offspring development and postnatal growth, and the effect of individual components is therefore presumed to depend on the concomitant effect of other components, as determined by their relative concentrations (Royle et al, 2001;Surai, 2002;Possenti et al, 2017Possenti et al, , 2018a. However, the combined as opposed to the independent effects of egg constituents have seldom been subjected to experimental analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we therefore investigated the combined effects of experimental manipulation of corticosterone and vitamin E concentration on embryo morphology and oxidative status in the yellow-legged gull (Larus michahellis Naumann 1840), a species that has previously been subjected to experimental investigation into the effects of diverse egg components in the wild (e.g. Rubolini et al, 2005;Parolini et al, 2015Parolini et al, , 2017aPossenti et al, 2017Possenti et al, , 2018a.…”
Section: Introductionmentioning
confidence: 99%
“…However, egg components are not expected to act independently in exerting their short-and long-term effects, as individual egg compounds are thought to act in concert in shaping offspring phenotype. For example, multiple antioxidants of maternal origin intervene in antioxidant defence processes and in regeneration of the antioxidant potential of individual antioxidant compounds, although their interactions are far from being fully understood (Surai, 2002; see also Possenti et al, 2017). Similarly, egg hormones are thought to participate in developmental and growth processes with independent as well as combined effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of functional interactions between egg components suggests that mothers should allocate compounds that are involved in interacting offspring physiological pathways in concentrations that reciprocally co-vary. A corollary expectation is that variation in the egg concentration of a specific compound should have effects that depend on the concentration of the other interacting molecules (Giraudeau and Ducatez, 2016;Possenti et al, 2017). While several studies have been carried out on the effect of individual egg components on offspring phenotype (e.g.…”
Section: Introductionmentioning
confidence: 99%